LEFT-SIDED POSTEROLATERAL DIAPHRAGMATIC HERNIA WITH ASSOCIATED INTESTINAL MALROTATION - Is Ikhsan Hataul; Suwardi Suwardi (Fakultas Kedokteran Universitas Pattimura, 2021)
Left-sided posterolateral diaphragmatic hernia is a defect in the diaphragm allowing the contents of the abdominal cavity to protrude into the thorax. The incidence has been reported between 1 in 2000 to 5000 births. In the United States, approximately 1000 infants are born with diaphragmhernia with a prevalence of 2.4 per 10,000 live births. The birth defect may be associated with other major anomalies and the lesion may become apparent in the fetus, newborn or older child. Malrotation is a one of anomaly which associated with diaphragmatic hernia. Some forms of diaphragmatic hernia remain asymptomatic and may not present until adulthood.